Special Section 301: US interference with the design and implementation of national patent laws - Carlos M. Correa (South Centre, 2020)
The continuous application of Special Section 301 by the Office of the United States Trade Representative (USTR) undermines the rule of law as a fundamental principle of a multilateral system based on the sovereign equality of states and the respect for international law. Interference with foreign countries' national intellectual property (IP) policies—which have significant socio-economic effects—negates their right to determine independently the level and modalities of protection of such property within the framework and policy space allowed by the international law. This paper examines the patent-related claims made by the USTR in relation to the developing countries on the USTR Priority Watch List. It argues that the regulations and practices identified by the USTR show a legitimate use of the flexibilities provided for by the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), and that the ignorance of the public interests of the countries concerned (for instance, with regard to access to affordable medicines) has contributed to the discredit (and ineffectiveness) of the Special Section 301.
Keywords: 300; Access to Medicines; Affordable Medicines; Algeria; Argentina; Biotechnological Products; Chile; China; Competition Law; Compulsory Licenses; Disclosure; Dispute Settlement; Evergreening; Flexibilities; GATT; Genetic Resources; India; Indonesia; Innovation; Intellectual Property; International Law; Multilateralism; Patent; Patent Examination; Patent Linkage; Patent Term; Patentability Criteria; Pharmaceuticals; sovereign equality; Traditional Knowledge; TRIPS; Unilateral Measures; United States (US); United States Trade Representative (USTR); US Special Section 301; USTR Priority Watch List; Venezuela; WIPO; World Intellectual Property Organization (WIPO); World Trade Organization (WTO); WTO